Antiproliferative And Apoptosis Effects Of Clinacanthus Nutans Leaf Extract On Breast Cancer Cell (Mcf7) - Ismail, Noor Zafirah (2023)
The objective of this study was to determine the antiproliferative and apoptotic effects of C. nutans leaf extract on the breast cancer cell line, Michigan Cancer Foundation-7 (MCF7).